One-pot chemo-enzymatic synthesis of furfuralcohol from xylose. (August 2017) - He, Yu-Cai; Jiang, Chun-Xia; Jiang, Ji-Wei; Di, Jun-Hua; Liu, Feng; Ding, Yun; Qing, Qing; Ma, Cui-Luan
Graphical abstract: Highlights: One-pot synthesis of furfuralcohol was conducted by chemo-enzymatic catalysis. Conversion of xylose to furfural with SO4 2− /SnO2 -MMT was optimized. Bioreduction of furfural to furfuralcohol with E. coli CCZU-K14 was optimized. Furfural liquor showed biocompatibility towards E. coli CCZU-K14 whole cells. Biosynthesis of furfuralcohol from 200 mM furfural was obtained at 100% yield. Abstract: Furfuralcohol (FOL) is an important intermediate for the production of lysine, ascorbic acid, and lubricants. It can be used as a hypergolic fuel in rocketry. In this study, it was attempted to synthesize FOL from xylose by tandem catalysis with solid acid SO4 2− /SnO2 -Montmorillonite and recombination Escherichia coli CCZU-K14 whole cells. Using SO4 2− /SnO2 -Montmorillonite (3.0 wt% dosage) as catalyst, a highest furfural yield of 41.9% was achieved from xylose at 170 °C for 20 min. Furthermore, Escherichia coli CCZU-K14 whole cells were used for bioconverting furfural to FOL. The optimum biocatalytic reaction temperature, reaction pH, cosubstrate concentration, and substrate concentration were 30 °C, 6.5, 1.5 mol glucose/mol furfural, and 200 mM, respectively. Finally, the yield of FOL from 200 mM furfural was achieved to 100% by Escherichia coli CCZU-K14 whole cells after 24 h. In conclusion, this strategy show high potential application for the effective synthesis of FOL.